2016
DOI: 10.1016/j.crme.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Some insights on the modelling of chip formation and its morphology during metal cutting operations

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…Especially, Rice and Tracey's expression became very popular in the fracture application and various researchers extended or modified the model to study the damage evolution. Johnson and Cook [28] extended this expression by considering separately the strain rate sensitivity and temperature dependency, which allowed a broad application of this model in a wide array of thermomechanical processes [5,8] . However, the work of Wierzbicki et al [29] proved that the approximation of the failure strain with a monotonically decreasing function of stress triaxiality is poor, while a strong dependency to the third stress invariant is to be preferred.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, Rice and Tracey's expression became very popular in the fracture application and various researchers extended or modified the model to study the damage evolution. Johnson and Cook [28] extended this expression by considering separately the strain rate sensitivity and temperature dependency, which allowed a broad application of this model in a wide array of thermomechanical processes [5,8] . However, the work of Wierzbicki et al [29] proved that the approximation of the failure strain with a monotonically decreasing function of stress triaxiality is poor, while a strong dependency to the third stress invariant is to be preferred.…”
Section: Introductionmentioning
confidence: 99%
“…Umer et al studied chip morphology predictions while machining hardened tool steel using finite element and smoothed particles hydrodynamics methods [32]. The topic of chip morphology and its formation modeling during metal cutting operations was also the subject of a study by Mabrouki et al [33].…”
Section: State Of the Artmentioning
confidence: 99%
“…Metals 2019, 9, x FOR PEER REVIEW 4 of 26 hydrodynamics methods [32]. The topic of chip morphology and its formation modeling during metal cutting operations was also the subject of a study by Mabrouki et al [33]. In chip machining, the chip forming process is often accompanied by the formation of a built-up edge (BUE) in the face of the tool and it is necessary to take this phenomenon into account.…”
Section: State Of the Artmentioning
confidence: 99%
“…They analysed various chip shapes by using different plastic displacement values and found that chip transition occurs from continuous to segmentation with increasing feeds. Mabrouki et al [2] investigated the characteristics of chip morphology and chip microstructures during cutting operation under high loading. Mabrouki et al [18] also investigated the dry cutting of an aeronautic aluminium alloy and developed the numerical model based on the Johnson-Cook law incorporating with material damage evolution by using a fracture energy model.…”
Section: Chip Formation Mechanism Using Finite Element Simulationmentioning
confidence: 99%
“…The continuous chip is often considered to be an ideal chip that generates stable cutting forces; however, it is not desired for automated machining because the continuous chips may obstruct the machining process, which may lead to unpredictable damage on the machined surface, cutting tool or machine tool. To minimize these problems, serrated chips that are easier to break and remove are preferred during machining [1] and [2], so, predicting the cutting conditions which lead to a serrated chip has become increasingly important.…”
Section: Introductionmentioning
confidence: 99%